Penyusunan Dokumen Mutu Laboratorium Guna Peningkatan Kualitas Pengelolaan Laboratorium di Sekolah Menengah Kejuruan Negeri (SMKN): Preparation of Quality Laboratory Documents to Improve the Quality of Laboratory Management in State Vocational Schools (SMKN) - Tri Candra Setiawati; Wachju Subchan; Sigit Prastowo; Basuki Basuki (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Vocational High Schools (SMK) in the learning process are supported by laboratories or workshops that provide competence to students. The existence of the Teaching Factory program as a result of cooperation between SMKN and industry is one factor that requires the school to prepare quality documents, competent laboratory managers, and skilled students. Therefore, well-organized Laboratory Management will benefit schools, students, laboratory users, and stakeholders. This activity aims to provide understanding and assistance in compiling laboratory quality documents that adopt the SNI ISO 17025:2017 quality management system. This system regulates testing laboratories and calibration laboratories, but it is very appropriate if adopted in several cases to be applied to educational laboratories, especially the preparation of laboratory quality documents. Community Service activities were conducted at SMKN 4 in Bondowoso Regency and SMKN 8 in Jember Regency. Based on the discussion and questionnaire results, the activity showed that at both SMKNs, the understanding of the laboratory quality management system increased (72.7%) for both students and managers (teachers and technicians/labor). Quality documents for levels 2, 3, and 4 at both SMKNs have been compiled. The number of Standard Operational Procedure (SOP) documents at SMKN 4 is 8 SOPs; at SMKN 8, as many as 31 SOPs are based on SNI ISO 17025:2017 laboratory QMS.